2017
DOI: 10.1016/j.watres.2017.10.028
|View full text |Cite
|
Sign up to set email alerts
|

Microbial activity influences electrical conductivity of biofilm anode

Abstract: This study assessed the conductivity of a Geobacter-enriched biofilm anode in a microbial electrochemical cell (MxC) equipped with two gold anodes (25 mM acetate medium), as different proton gradients were built throughout the biofilm. There was no pH gradient across the biofilm anode at 100 mM phosphate buffer (current density 2.38 A/m) and biofilm conductivity (K) was as high as 0.87 mS/cm. In comparison, an inner biofilm became acidic at 2.5 mM phosphate buffer in which dead cells were accumulated at ∼80 μm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 69 publications
(17 citation statements)
references
References 44 publications
0
17
0
Order By: Relevance
“…On the other hand, increasing biofilm thickness may cause both electron‐ and mass‐transport limitations within the biofilm and may even lead to the accumulation of inactive bacteria (i.e., bacteria that do not contribute to the electrode performance) below or on top of the metabolically active bacteria. The values that are usually reported for the biofilm thickness of Geobacter ‐dominated mixed‐culture EAB are in the range 100–200 μm . However, these values are generally reported without a discussion of the respective biofilm growth conditions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, increasing biofilm thickness may cause both electron‐ and mass‐transport limitations within the biofilm and may even lead to the accumulation of inactive bacteria (i.e., bacteria that do not contribute to the electrode performance) below or on top of the metabolically active bacteria. The values that are usually reported for the biofilm thickness of Geobacter ‐dominated mixed‐culture EAB are in the range 100–200 μm . However, these values are generally reported without a discussion of the respective biofilm growth conditions.…”
Section: Resultsmentioning
confidence: 99%
“…The values that are usually reportedf or the biofilm thickness of Geobacter-dominated mixed-cultureE AB are in the range 100-200 mm. [12,24,32,37,40] However,t hese values are generally reported without ad iscussion of the respective biofilm growth conditions. Biofilms growingu nder conditions limited by mass transfer are known to form porous structures with large surface areas.…”
Section: Long-term Biofilmg Rowth Behaviormentioning
confidence: 99%
“…On the one hand, the live cells of the two-layer structure were less than that of the viable single layer with the same biomass. On the other hand, although the dead inner layer in the two-layer structure will not inhibit electron transfer from the live outer layer to the electrode, the electrochemical activity of the outer layer cells will be impaired by the dead inner layer, resulting in an increase in the charge transfer resistance ( Sun et al, 2015 , 2017 ; Dhar et al, 2017 ). The gradual decrease in the A0 stable potential was very possibly caused by the accumulation of dead cells in the inner layer of the anode biofilm.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, enhanced substance diffusion [either the substrate or metabolic end products (H + )] can increase the biomass, viability and performance of the anode biofilm. It has been shown that using a highly concentrated phosphate-buffered saline (PBS) solution as the anode electrolyte or increasing the pH of the anode electrolyte from a weak acid (pH = 6–7) to alkalinity (pH = 7–9) to mitigate proton accumulation in the anode biofilm or adjusting the gravity settling of planktonic bacteria and bioanode can increase the biomass, viability and current generation of anode biofilms ( Liu et al, 2005 ; Cheng and Logan, 2007 ; Patil et al, 2011 ; Dhar et al, 2017 ; Li et al, 2017 ). In previous studies, we found that aerobically enriched anode biofilms with sufficient substance diffusion in the inner layer had a thicker inner layer and a higher current generation.…”
Section: Introductionmentioning
confidence: 99%
“…can be selectively enriched on electrode surface to form a thick anode biofilm (10s or even 100s of micrometers) upon electrochemical interactions with electrodes (Kumar et al, 2017). Several microscale investigations on anode biofilms have revealed inactive cells within biofilms, in their either outer or inner layers (Dhar et al, 2017; Renslow, Babauta, Dohnalkova, et al, 2013; Sun et al, 2015). These investigations are crucial to determine whether the cells inside the biofilms contribute to current generation.…”
Section: Introductionmentioning
confidence: 99%